2018
DOI: 10.1016/j.jasrep.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Local production and long-distance procurement of beads and pendants with high mineralogical diversity in an early Saladoid settlement of Guadeloupe (French West Indies)

Abstract: The preventive excavation of an archaeological site located at the Gare Maritime of Basse-Terre (Guadeloupe, French West Indies) revealed a series of stone artifacts including finished beads and pendants, as well as pieces representing several stages of the chaîne opératoire. This work is an integrated study of the mineralogy and typo-technology of these objects. The artifacts have been recovered from layers interpreted as midden deposits of an early Saladoid coastal settlement dated to 250-400 A.D. Non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
2
24
0
2
Order By: Relevance
“…Overviews of Early Ceramic Age lapidary circulation are continually revised as new data comes to light (Cody 1990(Cody , 1993Hofman et al 2007Hofman et al , 2014aKnippenberg 2007;Rodríguez López 1993). Lithic identification has involved the use of macroscopic examination, refractive index and specific gravity tests, petrography, SEM-EDS, XRD and Raman spectroscopy (Cody 1990, 46;Cody 1993;Hardy 2008, 223-226;Murphy et al 2000;Queffelec et al 2018;Watters and Scaglion 1994). However, the sources of most raw materials remain uncertain.…”
Section: Raw Materials Provenancementioning
confidence: 99%
See 1 more Smart Citation
“…Overviews of Early Ceramic Age lapidary circulation are continually revised as new data comes to light (Cody 1990(Cody , 1993Hofman et al 2007Hofman et al , 2014aKnippenberg 2007;Rodríguez López 1993). Lithic identification has involved the use of macroscopic examination, refractive index and specific gravity tests, petrography, SEM-EDS, XRD and Raman spectroscopy (Cody 1990, 46;Cody 1993;Hardy 2008, 223-226;Murphy et al 2000;Queffelec et al 2018;Watters and Scaglion 1994). However, the sources of most raw materials remain uncertain.…”
Section: Raw Materials Provenancementioning
confidence: 99%
“…Amethyst sources have been identified in Martinique and southeastern Amazonia (Cody 1993;Epstein 1988;Watters 1997). However, it is not clear whether the Antillean amethyst and turquoise sources were exploited, due to the small size of their products and the lack of evidence for local exploitation (Cody 1993;Knippenberg 2007, 168;Queffelec et al 2018). Jadeitite sources are known in the Motagua Fault Zone on Guatemala (Foshag and Leslie 1955;Harlow et al 2011), eastern Cuba (García-Casco et al 2009), and northern Dominican Republic (Schertl et al 2012).…”
Section: Raw Materials Provenancementioning
confidence: 99%
“…This project consisted in three workpackages, including chaînes opératoires studies, gemmology, and the creation of a regional database and GIS. More information on the other results obtained during this project can be found in (Queffelec et al 2018), (Queffelec et al 2020) and (Queffelec et al, n.d.).…”
Section: The Paaf Projectmentioning
confidence: 89%
“…Data about lapidary artifacts in the French islands of the Antillean (from south to north: Martinique, Guadeloupe, St. Barthelemy and St. Martin) have been registered thanks to missions in the museums, the storage of the Ministry of Culture, and by extracting some collections to study them in continental France. The detailed methodology is described in the case studies articles (Queffelec et al 2018(Queffelec et al , 2020 and includes mainly photography, classic measurements with digital caliper, technological study, and mineralogical determination by eye and systematically confirmed by Raman spectroscopy. The literature review, which accounts for the most part of the dataset, has been conducted as a longterm job.…”
Section: Stepsmentioning
confidence: 99%
“…The study of raw material acquisition, lithic reduction and the distribution and exchange of stone materials and artefacts has received an increasing attention during the past two decades in Caribbean archaeology (Bérard 2004: 159-179;García-Casco et al 2013;Harlow et al 2006;Knippenberg 2006;2011a;Rodríguez Ramos 2001;2010: 88-144;Queffelec et al 2018;Schertl et al 2018). The region's island setting and the inter-island variation in Journal of Lithic Studies (2020) vol.…”
Section: Introductionmentioning
confidence: 99%